IMPLEMENTATION OF LAW NUMBER 01 OF 2024 CONCERNING TAXES ON NON-METALLIC MINERALS AND ROCKS. (STUDY IN PASAR SELUMA VILLAGE, SOUTH SELUMA DISTRICT, SELUMA REGENCY) - Faizal Susanto; Mulyadi Gembar; Henny Aprianty (Yayasan Wayan Marwan Pulungan, 2025)
This research aims to find out how to implement tax policies on non-metallic minerals and rocks. The method used is descriptive qualitative using the theory of Van Meter and Van Horn (1975), defining Policy Implementation, as actions used by either individuals or groups, groups of government officials or the private sector, which are directed towards achieving a goal that has been outlined in an ongoing policy decision. Linearly from public policy, implementer policy performance. This qualitative descriptive method is used for what is carried out with the main aim of creating an objective picture or description of a situation, in this case, to see a picture of role conflict and intra-role conflict. The reason for choosing qualitative descriptive is knowing the constraints or obstacles to the results of this research. More implementation it is easy to get conclusions regarding the issue of distributing Policy Implementation of Law Number 01 of 2024 Tax on Non-Metal Minerals and Rocks The tax collection policy for non-metallic minerals and rocks is generally seen from a psychological perspective, namely consultations, services and inspections run well for tax compliance. Taxes used to increase from previous years, this is known from the realization of the targets set and there is an increase in realization every year.